2020
DOI: 10.1038/s41419-020-03171-9
|View full text |Cite
|
Sign up to set email alerts
|

LINC00174 is a novel prognostic factor in thymic epithelial tumors involved in cell migration and lipid metabolism

Abstract: Long non-coding RNAs are emerging as new molecular players involved in many biological processes, such as proliferation, apoptosis, cell cycle, migration, and differentiation. Their aberrant expression has been reported in variety of diseases. The aim of this study is the identification and functional characterization of clinically relevant lncRNAs responsible for the inhibition of miR-145-5p, a key tumor suppressor in thymic epithelial tumors (TETs). Starting from gene expression analysis by microarray in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…LncRNAs are over 200 nucleotides in length without protein-coding capacity, which play functional role through different mechanisms of action, according to their localization [ 22 , 25 ]. Cytoplasmic lncRNAs participate to post-transcriptional regulation, mRNA turnover, protein stability and modulation of signaling pathways [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs are over 200 nucleotides in length without protein-coding capacity, which play functional role through different mechanisms of action, according to their localization [ 22 , 25 ]. Cytoplasmic lncRNAs participate to post-transcriptional regulation, mRNA turnover, protein stability and modulation of signaling pathways [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent work revealed that non-coding RNA inhibits AML proliferation through selective RAB27B targeting [ 24 ]. Since long non-coding RNAs (lncRNAs) participate in transcriptional regulation within the cell and form regulatory networks [ 25 27 ], we sought to determine whether lncRNA was involved in MYC-driven leukemia proliferation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of their ability to bind to different molecules, lncRNAs functions are more complex than that of miRNAs. They can regulate many cellular processes, such as translation, splicing, and chromatin status, by interacting with RNA/DNA or influencing transcription factor stability and localization [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Significant advances have recently been made in the characterization of the molecular landscape at the basis of TET underlined by The Cancer Genome Atlas (TGCA) [ 10 ] data publication and the identification of the non-coding RNA contribution to TET-associated phenotype [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%